Simulation of the Thermal and Mechanical Effects of a Planar Rectangular High Intensity Ultrasound Transducer to Be Used for Destroying Atherosclerotic Plaque - Damianou, Christakis A.; Christofi, Christos; Mylonas, Nicos (My University, 2013)
The aim of this study is to perform a simulation study of the thermal and mechanical effects of a flat rectangular (3×10 mm2),MRI compatible transducer operating at 5 MHz for the purpose of destroying atherosclerotic plaque. The simulation study focuses on measuring the plaque destruction (due to the thermal of mechanical mode of ultrasound) as a function of power, time, frequency, duty factor and pulse duration. The main goal is to keep the artery temperature at a safe level. The simulation study shows that with the thermal mode the temperature in the artery cannot be kept at a safe level.
Keywords: Ultrasound; Atherosclerotic; Plaque; MRI